Give Goods or Give Money? The Influence of Cause-Related Marketing Approach on Consumers’ Purchase Intention - Ye, Shenghong; Liu, Yunxiao; Gu, Suizi; Chen, Haiquan (Frontiers in Psychology, 2021)
With the progress of social and improvement of public awareness, the demand for enterprises to participate in a social welfare cause is increasing. A company can directly support corporate social responsibility issues through cause-related marketing (CRM) approaches, for example, by donating part of the proceeds from product sales (i.e., buy-one give-money or BOGM) or simply by donating their products (i.e., buy-one give-one or BOGO). Previous research has only discussed the impact of one of these CRM approaches on customers in one study. This research compared the effect of these two approaches on the purchase intention of consumers. Experiment 1 demonstrated that, for practical products, the purchase intention of BOGO (vs. BOGM) was higher, while for hedonic products, the purchase intention of BOGM (vs. BOGO) was higher. More importantly, we found a potential mechanism – perceived helpfulness – that drives our main effect. Experiment 2 revealed that the different statement order of charity information and product information in advertising can moderate the main effect. The research also provides several implications and insight into how companies can make donations while winning more customers’ willingness to pay, thus encouraging more companies to fulfill their corporate social responsibility.